OPTIMIZATION OF REGIONAL TAX REVENUE IN THE ISLANDS REGION HALMAHERA SELATAN REGENCY - Rusdi Noh; Nahu Daud; Abdul Chalid Ahmad; Chairullah Amin (SEAN Institute, 2023)
Provincial taxes are one regional revenue source contributing to PAD in island-based areas. The research aims to identify the advantages and classify nine types of local taxes that have fast growth and are competitive based on the sub-district area in South Halmahera Regency during 2018-2021. The analytical method adopts the Location Quotient and Shift-Share analysis techniques commonly used in regional economic sector advantage analysis to determine the ideal type of tax. The results show that only three types of taxes are categorized as superior taxes in all sub-districts: PBB P2, tax on non-metallic minerals and rocks, and restaurant tax. The types of taxes in the SS-Tax analysis that have a fast growth rate and are highly competitive are the Restaurant tax, the Non-Metal and Rock Mineral tax, and the Street Lighting tax.